2020
DOI: 10.7150/jca.46461
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Efficacy of NBDHEX on Gefitinib-resistant Human Non-small Cell Lung Cancer

Abstract: Gefitinib, a first-generation EGFR tyrosine kinase inhibitor (EGFR-TKI), is recommended for treatment of non-small cell lung cancer (NSCLC) patients who harbor activating EGFR mutations. However, the tumors of most patients initially sensitive to gefitinib will develop resistance within several months of therapy. Drug resistance is a major obstacle to NSCLC treatment. The novel glutathione transferase P1 (GSTPi) inhibitor 6-(7-nitro-2, 1, 3-benzoxadiazol-4-ylthio) hexanol (NBDHEX) has recently been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This nitrobenzoxadiazole (NBD) derivative is a potent mechanism-based inhibitor of both human GSTP1-1 and GSTM2-2 and exhibits remarkable cytotoxicity towards various cultured cancer cell lines (IC50 values in the low micromolar/submicromolar range) [1]. Notably, in vivo studies demonstrated that NBDHEX has an excellent safety profile in mouse models and is orally active in mice bearing human cancer xenografts [2,3]; 1 is also highly cytotoxic in vitro towards the trophozoite stage of the protozoan parasite Giardia duodenalis, an activity related to its ability to inhibit parasite FAD-dependent glycerol 3-phosphate dehydrogenase and thioredoxin reductase [4][5][6]. This evidence paves the way to explore the potential of 1 in the treatment of other protozoan parasite infections.…”
Section: Introductionmentioning
confidence: 99%
“…This nitrobenzoxadiazole (NBD) derivative is a potent mechanism-based inhibitor of both human GSTP1-1 and GSTM2-2 and exhibits remarkable cytotoxicity towards various cultured cancer cell lines (IC50 values in the low micromolar/submicromolar range) [1]. Notably, in vivo studies demonstrated that NBDHEX has an excellent safety profile in mouse models and is orally active in mice bearing human cancer xenografts [2,3]; 1 is also highly cytotoxic in vitro towards the trophozoite stage of the protozoan parasite Giardia duodenalis, an activity related to its ability to inhibit parasite FAD-dependent glycerol 3-phosphate dehydrogenase and thioredoxin reductase [4][5][6]. This evidence paves the way to explore the potential of 1 in the treatment of other protozoan parasite infections.…”
Section: Introductionmentioning
confidence: 99%